2019
DOI: 10.3390/cancers11122001
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Architecture of Gliomagenesis–Genetic Risk Variants Linked to Specific Molecular Subtypes

Abstract: Genome-wide association studies have identified 25 germline genetic loci that increase the risk of glioma. The somatic tumor molecular alterations, including IDH-mutation status and 1p/19q co-deletion, have been included into the WHO 2016 classification system for glioma. To investigate how the germline genetic risk variants correlate with the somatic molecular subtypes put forward by WHO, we performed a meta-analysis that combined findings from 330 Swedish cases and 876 controls with two other recent studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
(77 reference statements)
0
12
0
Order By: Relevance
“…In the past decades, attention has been focused increasingly on the pathogenic mechanism involved in glioma 17,18 . Many lncRNAs have been associated with the risk of glioma, some of which have not been further studied, including CDKN2B‐AS1 19 . Here, we revealed for the first time that CDKN2B‐AS1 knockdown significantly inhibited the competitive phenotypes of glioma cells, including cell proliferation, invasion, migration, and apoptosis.…”
Section: Discussionmentioning
confidence: 81%
“…In the past decades, attention has been focused increasingly on the pathogenic mechanism involved in glioma 17,18 . Many lncRNAs have been associated with the risk of glioma, some of which have not been further studied, including CDKN2B‐AS1 19 . Here, we revealed for the first time that CDKN2B‐AS1 knockdown significantly inhibited the competitive phenotypes of glioma cells, including cell proliferation, invasion, migration, and apoptosis.…”
Section: Discussionmentioning
confidence: 81%
“…The development of unique molecular signatures of glioma with or without an IDH mutation will help to shed light on possible targets that could be exploited in the treatment of glioblastoma. This study aims to specifically identify co-occurring mutations and gene expression patterns in IDH1-mutant glioma using a genome-wide approach, with the aim to improve glioma genetic profiling and understand how an IDH1 mutation influences this [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses integrating expression quantitative trait loci QTL (eQTL) data with glioma GWAS have provided limited insights to date. One study used glioma datasets from The Cancer Genome Atlas (TCGA) and lymphoblastoid cell line data from Genetic EUropean VAriation in DISease (GEUVADIS) ( Lappalainen et al, 2013 ; Kinnersley et al, 2015 ); two others utilized brain tissue data of Genotype-Tissue Expression Project (GTEx), and one also used a blood eQTL dataset ( Westra et al, 2013 ; Melin et al, 2017 ; Wu et al, 2019 ). Among the three studies, significant target genes were identified in three loci using GTEx brain tissues but none using glioma tissues from TCGA ( Kinnersley et al, 2015 ; Melin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%